Empire and Jihad : the Anglo-Arab wars of 1870-1920 - Faulkner, Neil (New Haven : Yale University Press, 2021)
The Ottoman Sultan called for a "Great Jihad" against the Entente powers at the start of the First World War. He was building on half a century of conflict between British colonialism and the people of the Middle East and North Africa. Resistance to Western violence increasingly took the form of radical Islamic insurgency.0 0Ranging from the forests of Central Africa to the deserts of Egypt, Sudan, and Somaliland, Neil Faulkner explores a fatal collision between two forms of oppression, one rooted in the ancient slave trade, the other in modern "coolie" capitalism. He reveals the complex interactions between anti-slavery humanitarianism, British hostility to embryonic Arab nationalism, "war on terror" moral panics, and Islamist revolt. Far from being an enduring remnant of the medieval past, or an essential expression of Muslim identity, Faulkner argues that "Holy War" was a reactionary response to the violence of modern imperialism.
Introduction -- Part I. Black ivory, white Nile -- 1. Heart of darkness -- 2. The mountains of the moon -- 3. A ruckle of bones -- Part II. Star and crescent -- 4. Baker Pasha -- 5. Gordon Pasha -- 6. Egypt for the Egyptians? -- 7. All Sir Garnet -- Part III. The black flag -- 8. A Muslim prophet -- 9. A Christian mystic -- 10. A modern crusader -- Part IV. The spectre o f Jihad -- 11. An Islamic caliphate -- 12. Omdurman -- 13. A 'Mad Mullah' -- 14. The Kaiser's war -- Conclusion.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on July 28, 2021).
In English.
JSTOR
Keywords: Great Britain -- Colonies -- Africa -- History; Jihad -- History; Africa -- History -- 19th century; Africa -- History -- 1884-1918.; Great Britain -- Foreign relations -- Arab countries; Arab countries -- Foreign relations -- Great Britain; Grande-Bretagne -- Colonies -- Afrique -- Histoire; Jihād -- Histoire; Afrique -- Histoire -- 19e siècle.; Afrique -- Histoire -- 1884-1918.; Grande-Bretagne -- Relations extérieures -- États arabes; États arabes -- Relations extérieures -- Grande-Bretagne.; HISTORY / Europe / Great Britain / Victorian Era (1837-1901).; British colonies; Diplomatic relations; Jihad; Africa; Arab countries; Great Britain; 1800-1918; History